Repeated extraction of aphyric melts in a rhyolitic system revealed by zircon age and composition: the Ramadas Volcanic Centre (Puna plateau), NW Argentina - Bardelli, Lorenzo; Becchio, R.; Ortíz, A.; Schmitt, Axel Karl; Pereira, R.; Báez, W.; Reckziegel, F.; Viramonte, J.; Giordano, G. (Lithos, 2021)
Rhyolitic volcanism can provide important information about the mechanisms by which highly-evolved crystal-poor melts can be extracted from silicic crystal-mush reservoirs. In the Altiplano-Puna plateau (Central Andes), rhyolites are volumetrically less abundant than the high-volume, crystal-rich intermediate products emitted during the ignimbritic flare-up (ca. 10-1 Ma), and their geological and temporal relation with the widespread, upper crustal, dacitic mush systems is not well constrained. We studied the isotopic (UPb ages), trace (U, Th, Hf, Y, Ti, P) and rare earth element compositions of zircon contained in the rhyolitic products of the Ramadas Volcanic Centre (late Miocene), which erupted extremely-aphyric, garnet-bearing tubular pumice during a single Plinian event (Corte Blanco Tuff; northern Puna plateau). Results reveal a complex pre-eruptive magmatic history characterized by variable crystallization conditions existing at different times within an upper-crustal crystal-mush reservoir. The unmixing model applied to magmatic zircon sharing textural and geochemical features (oscillatory texture, Th/U = 0.2-0.6; Eu/Eu* = 0.1-0.7) indicates the existence of at least two mush-related crystallization events, which are separated by a protracted hiatus (ca. 2 Ma), and are supported by independent isotopic ages. An episode of zircon crystallization (average disequilibrium-corrected 206Pb/238U age of 9.06 ± 0.19 Ma) coincides with the ages determined for accessory phases associated with garnet in pumice samples (9.163 ± 0.037 Ma, UPb age determination on zircon; 8.70 ± 0.23 Ma, U-Th-Pb age determination on monazite). A further zircon crystallization event is recorded at ca. 6.64 ± 0.12 Ma, which is concordant with published radiometric ages dating the eruption at 6.3 ± 0.3 Ma (average 40Ar/39Ar age of glass shards from distal locations) and at 6.63 ± 0.28 Ma (fission track age of proximal obsidian). The existence of a late-stage to hydrothermal crystallization event is evident from another zircon population with low Th/U ratios (< 0.1) and a 206Pb/238U age of 6.514 ± 0.058 Ma, which crystallized in cold and highly-evolved parts of the reservoir resulting in negative Eu/Eu* and Ti depletion in zircon before these crystals were recycled into the erupting magma. The extreme aphyric character of the rhyolitic products and the nearly-complete lack of phenocrysts and glomerocrysts despite their evolved composition indicate that the Plinian eruption was preceded by effective extraction of crystal-poor melts from the mush zone, during which only micrometric antecrystic minerals (≤ 200 μm) were incorporated. Gas filter-pressing, combined with a compressional local stress field, likely contributed to melt-crystal separation, which was favoured by high volatile contents (H2Omelt 3-5 wt%) and shallow emplacement levels (< 10 km). Finally, the distribution of the U-Pb ages of zircon antecrysts suggests a correlation between the evolution of the Ramadas magmatic system and the fluctuating pattern characterizing the Altiplano-Puna Volcanic Complex flare-up activity, highlighting a possible geological and temporal connection between rhyolitic volcanism and the widespread dacitic mush systems in this sector of the Puna plateau.
Gesehen am 28.06.2021